Discover and explore San Isidro (Promoting Tourism through photography) - Tutor, Mae Joy N.
San Isidro, one of the municipalities of Davao Oriental, is considered to be a probable tourist destination because of its natural scenic spots, virgin falls, and long arrays of beaches just to name a few. These tourist destinations are primarily promoted through a brochure which appeared to be ineffective. With this presented problems, the production thesis ?Discover and Explore San Isidro! Promoting Tourism Through Photography? presents photography as means of promoting alternative tourism in San Isidro, particularly design for postcards. In conceptualizing the photographs, the concept of alternative tourism was used which stands in preserving the original rural appeal of the destination. Photography techniques were also incorporated in the conceptualization such as simplicity, camera angle, outdoor lighting, balance and center of interest. This production has produced ten photographs which illustrate the concept of alternative tourism as promotional material designed for postcards.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts